2017
DOI: 10.1038/s41598-017-18366-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of weathered polystyrene films in seawater microcosms

Abstract: A microcosm experiment was conducted at two phases in order to investigate the ability of indigenous consortia alone or bioaugmented to degrade weathered polystyrene (PS) films under simulated marine conditions. Viable populations were developed on PS surfaces in a time dependent way towards convergent biofilm communities, enriched with hydrocarbon and xenobiotics degradation genes. Members of Alphaproteobacteria and Gammaproteobacteria were highly enriched in the acclimated plastic associated assemblages whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 60 publications
5
79
0
Order By: Relevance
“…Such a band is particularly prominent in our PS Water spectra but also visible in the Biofilm samples of PS and PP. In addition to this band, Syranidou et al (2017) observed a broad band between 1,500 and 1,350 cm −1 for one of the weathered PS samples, which was absent in our samples. Taken together, our results indicate surface modifications of the PP and PS Biofilm samples that differ from those observed for the respective Water samples.…”
Section: Surface Chemistrysupporting
confidence: 46%
See 2 more Smart Citations
“…Such a band is particularly prominent in our PS Water spectra but also visible in the Biofilm samples of PS and PP. In addition to this band, Syranidou et al (2017) observed a broad band between 1,500 and 1,350 cm −1 for one of the weathered PS samples, which was absent in our samples. Taken together, our results indicate surface modifications of the PP and PS Biofilm samples that differ from those observed for the respective Water samples.…”
Section: Surface Chemistrysupporting
confidence: 46%
“…The reported maximum was at 1,735 or 1,712 cm −1 , which is different from the band positions observed in our study, which might be related to differences in both biotic and abiotic conditions. In fact, exposure to polymerdegrading microbes reduced at least some of the spectral changes caused by polymer degradation in PP (Auta et al, 2018) and PS (Syranidou et al, 2017). Moreover, in the latter study a broad band in the 1,200-900 cm −1 spectral range for one the of the weathered PS samples was reported.…”
Section: Surface Chemistrymentioning
confidence: 66%
See 1 more Smart Citation
“…PS was highly resistant to biodegradation by T. hamatum, the degradation rate after two months being only 0.9% (w/w) ( Table 3). The extremely low degradability of PS is in agreement with the reports of other authors [41].…”
Section: Biodegradation Of Polymer Plastic Films Measured By Gravimetsupporting
confidence: 93%
“…PS was highly resistant to biodegradation by T. hama being only 0.9% (w/w) ( Table 3). The extremely low de reports of other authors [41].…”
Section: Biodegradation Of Polymer Plastic Films Measured By Gramentioning
confidence: 85%